Trinitroglycerine-loaded chitosan nanoparticles attenuate renal ischemia-reperfusion injury by modulating oxidative stress - Zeinab Karimi; Khatereh Asadi; Pooran Ghahramani; Ahmad Gholami (Scientific Reports)
Abstract Renal ischemia-reperfusion (I/R) injury is a common clinical factor for acute kidney injury (AKI). A current study investigated the renoprotective effects of the trinitroglycerine (TNG) combination with chitosan nanoparticles (CNPs) on renal I/R-induced AKI. Rats were randomly assigned to five groups (n = 8/group): Sham, I/R, TNG (50 mg/kg) + I/R, CNPs (60 mg/kg) + I/R, and TNG-CNPs + I/R. Bilateral renal pedicles were occluded for 60 min to induce ischemia. TNG, CNPs, or TNG-CNPs were administered intraperitoneally 30 min before renal ischemia. After 24 h of reperfusion, blood samples were collected, and both kidneys were removed. The left kidney was used for oxidative stress analysis. The right kidney was preserved in 10% formalin for histopathological examination via H&E staining. After renal ischemia-reperfusion injury, there was an observed increase in plasma creatinine (Cr) and blood urea nitrogen (BUN), accompanied by a decrease in glomerular filtration rate (GFR) in rats. Total oxidative stress (TOS) levels were also significantly higher in the I/R group, whereas total antioxidative capacity (TAC) was reduced. Histopathological examination revealed damage in the kidneys of rats in the I/R group. Pretreatment with the TNG-CNP formulation before I/R increased plasma and tissue TAC levels in rats. It also corrected the renal histopathological changes and functional disorders induced by I/R injury, as evidenced by reduced Cr and BUN, increased GFR, and attenuated oxidative stress. The results suggest that the TNG-CNP combination provides renoprotective effects against I/R-induced AKI by improving antioxidant status and minimizing renal injury.